Determinantes da remuneração do spread de certificados de recebíveis do agronegócio no mercado brasileiro - Toledo, Roberta Correia Rabelo Tavares de (2016)
The main purpose of this study is to evaluate the factors whitch determine the spread of Certificado de Recebível do Agronegócio (CRA). The research sample is composed of all issues registered in ANBIMA between 2012 and May 2016. It was observed that spread is mainly influenced by the presence of credit enhancement/collateral, from the sector which receivables were originated, and from the securitization company. In a second and more detailed study, when the variables were added one at a time to test the model, the results indicated that both volume and subordination level were important factors to explain the spread. By including the rating variable, this becomes statistically significant, similarly as happens with the variable collateral, demonstrating that the subordination level reduces de spread of the issue, however with the addition of the collateral variable it no longer becomes statistically significant. The sign of the collateral variable is positive and demonstrates that the presence of credit enhancement is crucial for the issue to occurs. Finally, the securitization company variable proved to be relevant, indicating that the investor takes into consideration the securitization quality for pricing this asset.